Empowerment of Community Groups to Realize Food Security - Shobachiyah, Ilmi; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
The general background food security is a critical global challenge that influences community well-being and development. The specific background in rural contexts, community empowerment is vital for addressing food security issues; however, the mechanisms and dynamics of such empowerment are often underexplored. The knowledge gap while existing literature emphasizes the importance of empowerment, there is a lack of detailed studies focusing on specific strategies that effectively enhance community resilience in food security. The aims this research aims to describe and analyze the empowerment of community groups in achieving food security, using a case study approach in a specific rural area. Results the study reveals that key indicators—authority, confidence and competence, trust, opportunities, responsibilities, and support—play significant roles in empowering community groups, leading to improved food security outcomes. The novelty this research introduces a comprehensive framework that interlinks these indicators, providing new insights into their collective impact on community food security initiatives. The implications emphasize the necessity for sustained support from local governments and active community participation, advocating for collaborative efforts to enhance the effectiveness and sustainability of food security programs in rural communities. Highlights: Community empowerment is essential for achieving food security in rural areas. Key indicators for success include authority, trust, and support from local governments. A collaborative approach enhances the effectiveness of food security initiatives. Keywords: Community Empowerment, Food Security, Rural Development, Participatory Approach, Sustainable Agriculture